PENAKSIR RASIO REGRESI MENGGUNAKAN KOEFISIEN KURTOSIS DAN KOEFISIEN VARIASI UNTUK RATA-RATA POPULASI - Endah Dwi Jayanti; Arisman Adnan; Sigit Sugiarto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This paper studies three regression ratio estimators for population mean Y of the variable Y using information on two auxiliary variables X dan Z under simple random sampling without replacements. This discussion is a review from the article of Singh et al. [Statistics in Transition 10(1): 85-100]. All estimators are biased. The efficient estimator is the one with the minimum Mean Square Error (MSE), determined by comparing each type of the estimators.